PELAKSANAAN FUNGSI BADAN PERMUSYAWARATAN DESA (BPD) DALAM MENAMPUNG DAN MENYALURKAN ASPIRASI MASYARAKAT DI DESA PAUH ANGIT KECAMATAN PANGEAN KABUPATEN KUANTAN SINGINGI TAHUN 2019-2020 - Tiamur Dianti; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
ABSTRACT The Village Consultative Body is an institution that embodies democracy in the administration of village government. The Village Consultative Body can also be considered as the parliament in the village. The Village Consultative Body aims to strengthen village administration, so that it is able to mobilize it to actively participate in various village development activities. Identification of problems in research on the implementation of the functions of the Village Consultative Body (BPD) in accommodating and channeling community aspirations in Pauh Angit village, Pangean sub-district, Kuantan Singingi district in 2019-2020, namely, the BPD has not been maximal in accommodating and channeling community aspirations, it can be seen that the BPD has not provided a suggestion box and the book that records people's aspirations, the BPD is not present at the office to carry out its duties and functions. So that there are several aspirations of the people that are not accommodated and channeled. The purpose of this study was to find out how the functions of the Village Consultative Body (BPD) are implemented in accommodating and channeling the aspirations of the people in Pauh Angit village. This study uses a qualitative method that describes the data obtained through interviews and documentation. While the data sources used are primary data obtained directly from the research location, namely information submitted by informants, and secondary data related to research. The results of research on the implementation of the functions of the Village Consultative Body (BPD) in accommodating and channeling community aspirations in Pauh Angit village, Pangean sub-district, Kuantan Singingi district in 2019-2020 are that the implementation of the function of accommodating and channeling community aspirations is not in accordance with Ministry of Home Affairs Regulation NO.110 2016 concerning the Village Consultative Body (BPD) articles 34 and 36. Keywords: Village Consultative Body (BPD), Accommodating and channeling community aspirations